2021
DOI: 10.1007/s11482-021-09989-5
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of Parental Labor Migration on Children’s Mental Health in Rural China

Abstract: Utilizing data from the China Education Panel Survey, we investigated the effects of parental migration and its duration on children’s mental health in rural China. We obtained a sample of 3830 rural children, comprising 2769 children who lived with both parents, 512 children whose one parent had migrated, and 549 children whose both parents had migrated. The results of multiple regression and propensity score matching showed that absence of both parents was negatively correlated to children’s mental health, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…This verifies Hypotheses 1.2 and 2.1. On the other hand, MC may be confronted with lower emotional well‐being and poorer social networking because they receive less understanding and more strictness from their parents (Anthony et al, 2020; Jiang & Yang, 2019; Stevens & Vollebergh, 2007). This finding verifies Hypothesis 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This verifies Hypotheses 1.2 and 2.1. On the other hand, MC may be confronted with lower emotional well‐being and poorer social networking because they receive less understanding and more strictness from their parents (Anthony et al, 2020; Jiang & Yang, 2019; Stevens & Vollebergh, 2007). This finding verifies Hypothesis 3.…”
Section: Discussionmentioning
confidence: 99%
“…In the background of accelerated migration and market‐oriented reform of the urban housing system in China, when large numbers of migrants gather in the developed cities, social classes show gradual differentiation in terms of their housing location, and isolation of migrants from local residents becomes prominent (Jiang & Yang, 2019; Peng et al, 2020; Wang, Zhang, et al, 2019). Most of the immigrants live in a “village‐in‐the‐city” with poor standards of living.…”
Section: Migrant Children Left‐behind Children and Welfarementioning
confidence: 99%
“…For example, a CES-D sample item is "I felt that I could not shake off the blues even with help from my family or friends during the past week." Studies such as Jiang et al [42] and Jiang et al [43] adopted the CEPS mental health scale in their research. The Cronbach's alpha of mental unwellness in Grade 7 students was 0.827.…”
Section: Variables Academic Performance In Chinese Mathematics and En...mentioning
confidence: 99%
“…Studies worldwide have shown that, besides positive economic impacts or increased household incomes through remittances that also support LBC's education [10][11][12], parental migration negatively influences the lives of children left behind [4,12,13]. Left-behind children, especially those with both parents migrating, are reported to have higher emotional problems and are more likely to experience poor psychological wellbeing compared to their counterparts [14][15][16][17][18]. Studies in Asian countries such as China, Vietnam, Nepal, Thailand, and the Philippines, have reported that compared to children with non-migrating parents, LBC have higher levels of depression, anxiety, loneliness, and lower levels of self-esteem, and have been reported to experience reduced happiness [12,15,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…There is also a paucity of evidence on the children's own views and experiences of how the new daily life situations they encounter following parental migration influence their social and mental wellbeing [14,26]. Additionally, previous studies on the topic have mainly focused on examining the significance of the association of parental labour migration with poor mental health wellbeing of the LBC, with a paucity of indepth qualitative research seeking to explore and understand the mental health challenges that these children face [13,14,16,26,27]. Indonesia is a significant contributor to the international migrant workforce, with over four million Indonesian labour migrants employed in more than twenty-five countries globally [28].…”
Section: Introductionmentioning
confidence: 99%